Vegetative Propagation Technique in Hardwickia binata Through Air Layering - Gupta, V.K.; Kumar, R.V.; Datta, A.; Solanki, K.R. (Indian Journal of Agroforestry, 2020)
Hardwickia binata Rxob., commonly known as Anjan, is an important tree species for agroforestry systems since it has straight bole with compact crown which permits sufficient sunlight to fall on ground for the growth of under storey crops. Asexual regeneration including micro propagation has not yielded appreciable result. Efforts on to standardized vegetative propagation technique in this species is being carried out at National Research Centre for Agroforestry, Jhansi since 1998 with application of different treatments. The best result was obtained with combination of 2000 ppm IBA + 2000 ppm NAA+500 ppm kinetin +500ppm vitamin B complex (2: 1:1:0:2 =v/v) which resulted in 100 per cent vigorous callusing with 60 per cent rooting and 100 percent survival of rooted branches in plastic pots.